2006
DOI: 10.1111/j.1365-246x.2005.02818.x
|View full text |Cite
|
Sign up to set email alerts
|

Seismological criticality concept and percolation model of fracture

Abstract: S U M M A R YIn the present paper we consider an anisotropically correlated percolation model of fracture (PMF), namely, the geometry of fracture structures, the energy emission model and the evolution of scatter of emitted (effective) amplitudes at attaining the critical point (CP; percolation threshold). The sequences of effective amplitudes calculated from PMF are considered as proxies of seismic catalogues and are analysed by various linear and non-linear methods, developed in modern time-series analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…The final rupture can be predicted by monitoring the process of clustering of small faults (Chelidze, 1982). The same conclusion was reached in the case of anisotropical geometry of fracture structures (Chelidze et al, 2006). Some hybrid models appeared that integrated CP and SOC theories.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…The final rupture can be predicted by monitoring the process of clustering of small faults (Chelidze, 1982). The same conclusion was reached in the case of anisotropical geometry of fracture structures (Chelidze et al, 2006). Some hybrid models appeared that integrated CP and SOC theories.…”
Section: Introductionmentioning
confidence: 66%
“…Let us take a look at the changes in the seismic situation near the epicenters of the Kronotskoe and Simushirskoe earthquakes over several years preceding these events. The power law acceleration of acoustic emission before fracture and foreshocks acceleration before earthquakes as the signs of criticality was given in (Chelidze, 1982;Chelidze et al, 2006). A practical useful approach to describe possible acceleration of the seismic process prior to an earthquake was offered in (Varnes, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the problem of fracture of heterogeneous media corresponds mathematically to problems of the percolation theory, which describe quantitatively the connectivity of components in a non-homogeneous system (Chelidze, 1979(Chelidze, , 1980a(Chelidze, , b, 1982(Chelidze, , 1986(Chelidze, , 1987(Chelidze, , 1993Chelidze at al., 2006;Arbadi and Sahimi 1990). It appears that the elastic modulus, M, decreases from the initial value for an intact lattice over nearly five orders of magnitude according to the expression M ∝ M 0 (x − x cr ) −3.6 , where x is the current concentration of breakages and x cr is the percolation threshold for a given finite system; it has been found that x cr = 0.494.…”
Section: On the Dependence Of The Fracture-induced Emission Pattern Omentioning
confidence: 99%
“…(8) has been also investigated based on the percolation model (e.g. Chelidze, 1993;Xie, 1993;Main, 1999;Chelidze et al, 2006).…”
Section: Damage and Porosity Evolutions In Rocksmentioning
confidence: 99%